2016
DOI: 10.1007/8904_2016_559
|View full text |Cite|
|
Sign up to set email alerts
|

Leigh-Like Syndrome Due to Homoplasmic m.8993T>G Variant with Hypocitrullinemia and Unusual Biochemical Features Suggestive of Multiple Carboxylase Deficiency (MCD)

Abstract: Leigh syndrome (LS), or subacute necrotizing encephalomyelopathy, is a genetically heterogeneous, relentlessly progressive, devastating neurodegenerative disorder that usually presents in infancy or early childhood. A diagnosis of Leigh-like syndrome may be considered in individuals who do not fulfil the stringent diagnostic criteria but have features resembling Leigh syndrome.We describe a unique presentation of Leigh-like syndrome in a 3-year-old boy with elevated 3-hydroxyisovalerylcarnitine (C5-OH) on newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Moreover, phenotypic heterogeneity has been recorded in m.8993T>G carriers [61,62]. Our study supports the literature which displays the occurrence of m.8993T>G mutation in sporadic cases with rapid segregation toward homoplasmy [63][64][65]; it is noticeable in a single generation and reported in about 1/5 LS cases [66]. Other differential diagnoses for LS were excluded [67][68][69].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, phenotypic heterogeneity has been recorded in m.8993T>G carriers [61,62]. Our study supports the literature which displays the occurrence of m.8993T>G mutation in sporadic cases with rapid segregation toward homoplasmy [63][64][65]; it is noticeable in a single generation and reported in about 1/5 LS cases [66]. Other differential diagnoses for LS were excluded [67][68][69].…”
Section: Discussionsupporting
confidence: 89%
“…Changes in the spectrum of organic acids are relatively non-specific and include high concentrations of the Krebs cycle metabolites: 2-hydroxyisobutyrate, 3-hydroxybutyrate, 2-oxoglutaric acid, lactate, pyruvate, fumarate, succinate, etc. In cases with PDHA1 -associated LS, a high level of alanine in blood is frequently observed and for the m.8993T>C/G variant low citrulline in blood (2/10; 20%) was noted which was previously reported in the literature [ 21 ].…”
Section: Discussionmentioning
confidence: 67%
“…These disorders classically present with severe, life‐threatening hyperammonemia in the newborn period; however, early identification and medical management of affected individuals can dramatically improve outcomes. Decreased citrulline is also a feature of certain mitochondrial disorders (Atkuri et al, 2009), including MT‐ATP6 mitochondrial disease (Balasubramaniam et al, 2016; Larson et al, 2019; Mori et al, 2014; Peretz et al, 2021), such that affected individuals may similarly be identified through NBS. Like proximal UCDs, MT‐ATP6 mitochondrial disease can have a severe neonatal presentation, and therefore the ability to efficiently identify and differentiate these disorders is important for providing appropriate medical management to symptomatic newborns, as well as guidance for family members.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports of infants diagnosed with MT‐ATP6 mitochondrial disease after initially presenting in metabolic crisis with features of Leigh syndrome for whom a NBS abnormality was reported (Balasubramaniam et al, 2016; Larson et al, 2019; Mori et al, 2014). Such reports have aided in the recognition of NBS abnormalities associated with MT‐ATP6 mitochondrial disease, which include various permutations of decreased citrulline, elevated 3‐hydroxyisovaleryl‐(C5‐OH) and/or propionyl‐(C3) acylcarnitine(s), with variability likely reflecting differences in NBS panels and cutoff levels between states.…”
Section: Introductionmentioning
confidence: 99%